PENGARUH KOMUNIKASI PEMASARAN YANG TERPADU TERHADAP KEPUASAN DAN LOYALITAS NASABAH PADA TABUNGAN SIAGA PT BANK BUKOPIN CABANG PEKANBARU - MARJUKI, ISMAIL (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The aim of study is to investigate direct and indirect effects of integrated marketing communication toward customer satisfaction and customer loyalty. The population are customers of Siaga Saving Account PT Bank Bukopin Tbk Pekanbaru Branch. The sample consisted of 200 customer who were selected with a convenience sampling technique. The variables are advertising, direct marketing, sales promotion,personal selling and public relation as independent variables, customer loyalty as dependent variable and customer satisfaction as an intervening variable. The data were analyzed with Fishbein analysis and path analysis by using SPSS 17 for windows. The results show that personal selling and public relation gives a positive and significant impact to both customer satisfaction or customer loyalty. Meanwhile, advertising, direct marketing, and sales promotion gives no significant impact to customer satisfaction and customer loyalty. Customer satisfaction no signifikan influences customer loyalty.It is recommended to depelove integrated marketing communications especially personal selling and public relation to make a good relationship with the customer and focused on market segmentation to promote a kind of product on create anew customer and have a good relationship with existing customer. Keywords: Integrated Marketing Communicatin, Customer Satisfaction and Customer loyalty